2018
DOI: 10.1039/c8ra00845k
|View full text |Cite
|
Sign up to set email alerts
|

Anticorrosive behavior of a zinc-rich epoxy coating containing sulfonated polyaniline in 3.5% NaCl solution

Abstract: An epoxy zinc-rich composite coating containing self-doped conducting sulfonated polyaniline (SPANi) nanofiber was prepared and the corrosion resistance of as-prepared coatings on Q235 substrate studied by open circuit potential (OCP), electrochemical impedance spectroscopy (EIS) and scanning vibrating electrode technique (SVET). Results suggested that a zinc-rich coating with addition of 1.0 wt% SPANi could enhance the cathodic protection time and barrier performance. To study corrosion diffusion, artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…The polyaniline benzenoid diamines, quinoid diamine, pyridine, and tertiary nitrogen non-bonding electrons lead to the chemisorption on the alloy surface. 56,57 Hence, the polyaniline fragment DE 1.0445 eV values are decreased and electrostatic potential 9743.6185 a.u values is increased indicates that polyaniline adsorbed on nickel alloy surface. In addition, positive charge of polyaniline nitrogen atom can improve the physisorption on the alloy surface to control the hydrogen evolution.…”
Section: Rsc Advances Papermentioning
confidence: 98%
“…The polyaniline benzenoid diamines, quinoid diamine, pyridine, and tertiary nitrogen non-bonding electrons lead to the chemisorption on the alloy surface. 56,57 Hence, the polyaniline fragment DE 1.0445 eV values are decreased and electrostatic potential 9743.6185 a.u values is increased indicates that polyaniline adsorbed on nickel alloy surface. In addition, positive charge of polyaniline nitrogen atom can improve the physisorption on the alloy surface to control the hydrogen evolution.…”
Section: Rsc Advances Papermentioning
confidence: 98%
“…Some studies suggest that PANI can release anions when the coating is damaged which leads to a second physical barrier that impedes the penetration of the aggressive agents. This mechanism is clearly illustrated by Wessling [30][31][32], Schauer et al [33], Sathiyanarayanan et al [34], and Nguyen et al [35]. Some other suggestions about the corrosion protection improvement of Zn-based functional layers have been elaborated in [36].…”
Section: Introductionmentioning
confidence: 94%
“…Malshe and Waghoo have proposed that gloss reduction in the epoxy coating may be due to the degradation of the aromatic matrix and secondary hydroxyl groups [48]. Yang and his coworkers have reported that the marine environment has caused a higher reduction in the gloss of the applied coating as compared to the salt spray testing due to sunlight and harsh atmospheric pollutants [49]. Bano and coworkers have also observed that in the epoxy coating, maximum gloss reduction was after natural exposure testing compared to salt spray testing [43].…”
Section: Gloss Measurementmentioning
confidence: 99%